Angiographic CT after Intravenous Contrast Agent Application: A Noninvasive Follow-Up Tool after Intracranial Angioplasty and Stenting - Psychogios, M.-N.; Schramm, P.; Buhk, J.-H.; Xyda, A.; Gröschel, K.; Jung, K.; Knauth, M. (American Journal of Neuroradiology, 2010)
BACKGROUND AND PURPOSE: ICAS is one of the therapeutic options in symptomatic cerebral artery stenosis. iaDSA is the current criterion standard examination after ICAS for the detection of ISR. In this study, we evaluated ivACT as a potential noninvasive follow-up alternative. MATERIALS AND METHODS: In 17 cases, ivACT and iaDSA were performed after ICAS. Both procedures were carried out on a flat-panel-detector-equipped angiography system. Postprocessing of ivACT acquisitions was performed on a dedicated workstation producing multiplanar reformations of the stent region and other intracranial arteries. Restenotic lesions were compared with iaDSA measurements. All studies were independently evaluated by 2 experienced neuroradiologists blinded to patients data. RESULTS: In 5 cases, ISR was diagnosed on iaDSA images. All restenotic lesions were reliably detected (sensitivity, 100%; 95%CI, 48%–100%) and could be correctly quantified on ivACT images in comparison with iaDSA. The neuroradiologists correctly excluded ISR in 11 of 12 lesions after viewing the ivACT examinations (specificity, 92%; 95%CI, 62%–100%). Measurements of ISR on ivACT were highly correlated to iaDSA (Pearson r = 0.94, P < .01). CONCLUSIONS: IvACT is a promising noninvasive follow-up examination after ICAS. With its high spatial resolution, it can reliably detect or exclude ISR. Contrary to iaDSA, there is no need for a recovery period after ivACT and the risk of neurologic complications is practically lowered to zero. A2second segment of anterior cerebral arteryACTangiographic CTBAbasilar arteryC3third segment of ICACIconfidence intervalCTDIwweighted CT dose indexΔDSA%change of stenosis percentage at follow-up iaDSA compared with measurements on iaDSA after stentingDSApostdigital subtraction angiography after stentingDSApredigital subtraction angiography before stentingDWIdiffusion-weighted imagingIAfocal lesion involving the end of the stentiaDSAintra-arterial digital subtraction angiographyIBfocal lesion involving the body of the stentICmultiple restenotic foci involving <50% of the stented segmentICAinternal carotid arteryICASintracranial artery angioplasty and stentingIIdiffuse intrastent lesionISRin-stent restenosisivACTACT after intravenous contrast medium applicationM1first segment of middle cerebral arteryMDCTAmultidetector CT angiographyPTApercutaneous transluminal angioplastyrePTArepeated PTA after ICASTIAtransient ischemic attackV4intracranial segment of vertebral artery